2013
DOI: 10.1080/02699931.2013.789792
|View full text |Cite
|
Sign up to set email alerts
|

The interactive roles of parenting, emotion regulation and executive functioning in moral reasoning during middle childhood

Abstract: We examined mother-child cooperative behavior, children’s emotion regulation and executive function, as well as combinations of these factors, as predictors of moral reasoning in 89 10-year-old children. Dyadic cooperation was coded from videotaped observations of laboratory puzzle and speech tasks. Emotion regulation was derived from maternal report, and executive functioning was assessed with the Tower of London task. Moral reasoning was coded during mother-child conversations about morally ambiguous, peer-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 30 publications
2
56
0
1
Order By: Relevance
“…Consistently, empirical research has demonstrated that parent–child positive synchrony is associated with children's adaptive self‐regulation, with effect sizes ranging from small to large (Kochanska et al., ; Laible & Thompson, ; Suveg, Shaffer, & Davis, ). These results have been replicated across several types of synchrony (e.g., shared positive affect, cooperation on a task; Hinnant, Nelson, O'Brien, Keane, & Calkins, ; Kochanska, Aksan, & Koenig, ) and self‐regulation (e.g., effortful control, committed compliance; Laible & Thompson, ; Pesonen et al., ).…”
Section: Youth Self‐regulationmentioning
confidence: 82%
“…Consistently, empirical research has demonstrated that parent–child positive synchrony is associated with children's adaptive self‐regulation, with effect sizes ranging from small to large (Kochanska et al., ; Laible & Thompson, ; Suveg, Shaffer, & Davis, ). These results have been replicated across several types of synchrony (e.g., shared positive affect, cooperation on a task; Hinnant, Nelson, O'Brien, Keane, & Calkins, ; Kochanska, Aksan, & Koenig, ) and self‐regulation (e.g., effortful control, committed compliance; Laible & Thompson, ; Pesonen et al., ).…”
Section: Youth Self‐regulationmentioning
confidence: 82%
“…Despite being frequently proposed as a major driving force of early moral development, parenting has received little empirical attention in this literature (Hinnant et al, 2013;Malti et al, 2013). Parent-child interactions constitute mutual and reciprocal forces of socialization that promote cooperation between children and their caregivers (Kochanska & Thompson, 1997), and the quality of this cooperation is believed to support and promote the emergence of self-regulated conduct (Thompson, 2014).…”
Section: Parenting Influences On Child Self-regulated Conductmentioning
confidence: 99%
“…When children are approximately 2 years of age, parents gradually expand their focus from primary care to incorporate educational components, for instance, teaching their children rules of behaviour; children thus begin to distinguish right from wrong and begin to regulate their behaviour in line with this understanding (Lamb & Lewis, 2004). There is, however, surprisingly little empirical support for this proposition (Hinnant, Nelson, O'Brien, Keane, & Calkins, 2013;Malti, Eisenberg, Kim, & Buchmann, 2013), and even less concerning the specific role of fathers (Grusec, Chaparro, Johnston, & Sherman, 2014). There is, however, surprisingly little empirical support for this proposition (Hinnant, Nelson, O'Brien, Keane, & Calkins, 2013;Malti, Eisenberg, Kim, & Buchmann, 2013), and even less concerning the specific role of fathers (Grusec, Chaparro, Johnston, & Sherman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The use of moral reasoning to justify actions or resolve moral dilemmas, as compared to reasoning based on sanctions, hedonistic or self-serving considerations, has also been demonstrated to predict specific types of prosocial responding in children, such as sharing, helping, and cooperation (Larrieu and Mussen, 1986; Miller et al, 1996; Stewart and McBride-Chang, 2000; Hinnant et al, 2013). Together, moral reasoning and moral emotions, such as sympathy and guilt, have been theorized to play an important role in the early development of moral action tendencies and the consideration of others’ welfare (Hoffman, 2000; Arsenio, 2014; Malti and Ongley, 2014).…”
Section: Introductionmentioning
confidence: 99%